2014
DOI: 10.1310/tsr21s1-s17
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy for the Treatment of Poststroke Plantar-Flexor Muscles Spasticity: A Prospective Open-Label Study

Abstract: ESWT is safe and efficacious for the treatment of poststroke plantar-flexor muscles spasticity, reducing muscle tone and improving passive ankle dorsiflexion motion. The effect was long lasting in subjects with echo intensity of calf muscles graded I, II, or III but was brief for echo intensity graded IV on the Heckmatt scale. The ESWT effect did not appear to be related to spinal excitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 16 publications
6
62
0
1
Order By: Relevance
“…Apparently with more time past the stroke, the changes in muscle architecture become more similar to the changes of an atrophic muscle [16]. It was revealed that the gastrocnemius muscle is the most susceptible muscle of the lower extremity to non-use which was detected by the changes in the muscle architecture [27].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Apparently with more time past the stroke, the changes in muscle architecture become more similar to the changes of an atrophic muscle [16]. It was revealed that the gastrocnemius muscle is the most susceptible muscle of the lower extremity to non-use which was detected by the changes in the muscle architecture [27].…”
Section: Discussionmentioning
confidence: 97%
“…The positive effect of ESWT on spasticity reduction in different upper motor neuron diseases such as cerebral palsy [7][8][9][10], stroke [11][12][13][14][15][16] and multiple sclerosis [17] has been shown in previous studies. Positive effect of ESWT on the feet plantar surface contact has been also shown in studies which applied ESWT over the spastic ankle plantar flexor muscles [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessity of new noninvasive treatment methods for spasticity has been raised because spasticity cannot be controlled sometimes even with diverse treatment methods as well as due to the existing side effects of oral drugs and the invasiveness of local treatment methods [12]. Recent studies indicated that shock wave therapy (SWT) is an effective method for treating spasticity, it is being considered as a new alternative treatment method for spasticity [13][14][15][16][17][18]. The radial SWT is a new noninvasive alternative therapeutic method based on technology generating non-focused shockwaves.…”
mentioning
confidence: 99%
“…The most important parameter of SWT for the outcome of treatment is the energy [23]. Different energy levels have been used in the previous studies for treatment of spasticity without any proven clinical benefits for certain energy level over the other [13][14][15][16][17][18][19][20][21][22]. So, the purpose of the study was to compare the effect of two different energy levels of radial SWT on spastic muscles of the hand and wrist in patients affected by stroke.…”
mentioning
confidence: 99%